Evaluating spatial analysis of tuberculosis prevalence to identify priority districts or municipalities that need policy attention in West Java - Emilia Pandin Madao; Hermawati, Ema; Putri, Nur A’isyah Amalia; Makful, Martya Rahmaniati (Universitas Gadjah Mada, 2024)
Purpose: This study assesses the spatial autocorrelation of tuberculosis (TB) with population density, poverty, personal hygiene and environmental sani- tation (perilaku hidup bersih sehat, PHBS), and housing quality to identify critical areas for targeted TB management in West Java. Methods: This ecological study analyzes secondary data from all TB patients across 27 regencies/cities in West Java Province for 2022. Spatial patterns were examined using the Global Moran's Index and Local Indicators of Spatial Association (LISA). Results: The analysis revealed significant clustering of TB prevalence with population density (p-value = 0.001) and PHBS (p-value = 0.047). At the same time, dispersion was noted with poverty (p-value = 0.355) and a non-significant clustering with housing quality (p-value = 0.270). Notably, ten regencies/cities exhibited significant local spatial autocorrelat- ion, indicating priority areas for intervention. Conclusion: TB prevalence in West Java show a positive spatial correlation with population density and PHBS, indicating clustered patterns that necessitate focused policy attention. The absence of a spatial correlation between poverty and housing quality suggests different intervention strategies may be required. TB intervention should be prioritized in areas like Bekasi Regency, Bekasi City, Bogor Regency, Bogor City, Cianjur Regency, and Depok City, where TB prevalence is significantly associated with key spatial factors.